Analysis of steady flow for various cerebral aneurysm size - Mohd Zamri, Deraman (2009)
Investigation on the changes of flow patterns in a blood vessel with a fixed fusiform aneurysm resulting from placement of a different size of aneurysm. The velocity profile and pressure distribution had been analysis from different size of aneurysm. Three different modeling of aneurysm had been analysis which is small, large, and giant. The diameter of small aneurysm is less 12mm. For the large aneurysm is between 12mm to 25mm of diameter. The giant sizes are about more 25mm in diametr. To identify the changes in local hemodynamics due to stent implantation, a stented and non stented aneurysm model was taken into considerations. The simulation of the model was studied under incompressible, Non-Newtonian, viscous, non pulsatile condition in which we investigated computationally in a three-dimensional configuration using a fluid dynamics program. Hence, the different size of aneurysm produces the different results of flow field in aneurysm. The velocity gets with different analysis from different size of diameter aneurysm. Different pressure distribution is feature from aneurysm that have different diameter. Aneurism that have big diameter will show changes in the pressure distribution graph. However, aneurysm that have small diameter can be detected using special device. Research and analysis parameter or other factor that influence flow in the aneurysm must be consider in future research.